Selera Humor dan Kepuasan Pernikahan pada Pasangan Menikah - Natasya, Meutia; Khairani, Maya; Dahlia, Dahlia; Amna, Zaujatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
Marital satisfaction is one of the important factors in order to stabilize the couple's relationship, shape the welfare in the family, the length of the marriage age and can reduce the risk of divorce. One of the things you can do to increase marital satisfaction is to share your sense of humor with your partner. The most important role of humor in marriage lies in increasing intimacy, strengthening bonds, and forming healthier marriages. This study aims to determine the relationship between sense of humor and marital satisfaction in married couples. This quantitative research method involved 60 married couples (120 people) who have children with a marriage age range of (1-10) years who live in Banda Aceh. Research data collection was carried out using two measuring tools, namely Multidimensional Sense of Humor (MSHS) and ENRICH Marital Satisfaction (EMS). The results of data analysis showed a significant value p=0.000 (p <0.05. R 0.255). This can be interpreted that there is a relationship between sense of humor and marital satisfaction in married couples, the higher the sense of humor, the higher the marital satisfaction.